STRATEGIC KNOWLEDGE MANAGEMENT FOR THE PERUVIAN COMPANIES - Pastor Carrasco, Carlos Alberto (2010)
Strategic Knowledge Management requires a balance between employee knowledge and technological resources available, defining the company’s competitiveness. This document presents proposals for solutions applicable to knowledge management and better use of available resources, optimizing the decision cycle in business, providing greater flexibility to the information flow and reducing costs. The main difficulties of the companies are in the identification and valuation of intellectual capital, in the absence of a policy to promote the ideas of an organizational culture for knowledge and technology investments to work at the strategic level. The restructuring of the organization, along with a shift to a new culture, creating knowledge enterprises. The appearance of the rapid expansion of technologies for the distribution and dissemination of information and knowledge has led to focus the opportunities for developing knowledge-based networks, knowledge sharing and knowledge management technologies and their potential applications improve the productivity of knowledge work. Difficult and complex problems in the future can be best addressed through the development of knowledge management as a discipline based on an integrative synthesis of hard and soft sciences. A management company of professional knowledge can provide a framework to support the development of the synthesis of proposals and serve as a focal point for coordination of professional activities in strategic areas of education, research and technological development. Preliminary concepts for developing the knowledge management discipline and professional society explored.